Amifostine reduces the seminiferous epithelium damage in doxorubicin-treated prepubertal rats without improving the fertility status - Vendramini, Vanessa; Cerri, Estela Sasso [UNESP]; Miraglia, Sandra M. (Springer Nature, 2010)
Background: Amifostine is an efficient cytoprotector against toxicity caused by some chemotherapeutic drugs. Doxorubicin, a potent anticancer anthracycline, is known to produce spermatogenic damage even in low doses. Although some studies have suggested that amifostine does not confer protection to doxorubicin-induced testicular damage, schedules and age of treatment have different approach depending on the protocol. Thus, we proposed to investigate the potential cytoprotective action of amifostine against the damage provoked by doxorubicin to prepubertal rat testes (30-day-old) by assessing some macro and microscopic morphometric parameters 15, 30 and 60 days after the treatment; for fertility evaluation, quantitative analyses of sperm parameters and reproductive competence in the adult phase were also carried out.Methods: Thirty-day-old male rats were distributed into four groups: Doxorubicin (5 mg/kg), Amifostine (400 mg/kg), Amifostine/Doxorubicin (amifostine 15 minutes before doxorubicin) and Sham Control (0.9% saline solution). Standard One Way Anova parametric and Anova on Ranks non-parametric tests were applied according to the behavior of the obtained data; significant differences were considered when p < 0.05.Results: The rats killed 30 and 60 days after doxorubicin treatment showed diminution of seminiferous epithelium height and reduction on the frequency of tubular sections containing at least one type of differentiated spermatogonia; reduction of sperm concentration and motility and an increase of sperm anomalous forms where observed in doxorubicin-treated animals. All these parameters were improved in the Amifostine/Doxorubicin group only when compared to Doxorubicin group. Such reduction, however, still remained below the values obtained from the Sham Control group. Nevertheless, the reproductive competence of doxorubicin-treated rats was not improved by amifostine pre-administration.Conclusions: These results suggest that amifostine promotes a significant reduction of the doxorubicin long-term side effects on the seminiferous epithelium of prepubertal rats, which is reflected in the epidydimal fluid parameters in the adult phase. However, fertility status results suggest that such protection may not be effective against sperm DNA content damage. Further investigation of sperm DNA integrity must be carried out using amifostine and doxorubicin-treated experimental models. © 2010 Vendramini et al; licensee BioMed Central Ltd.
Keywords: amifostine; DNA; doxorubicin; sodium chloride; antineoplastic antibiotic; radioprotective agent; animal cell; animal experiment; animal model; animal tissue; cell differentiation; cell protection; controlled study; DNA content; DNA damage; DNA determination; epididymis; female; male; male fertility; mating; microscopy; morphometrics; nonhuman; prepuberty; rat; reproduction; semen abnormality; seminiferous tubule epithelium; spermatogonium; spermatozoon count; spermatozoon motility; testis injury; animal; chemically induced disorder; down regulation; drug effect; evaluation; fertility; health status; pathology; physiology; pregnancy; semen analysis; sexual maturation; testis disease; Wistar rat; Animalia; Rattus; Amifostine; Animals; Antibiotics, Antineoplastic; Cytoprotection; Down-Regulation; Doxorubicin; Female; Fertility; Health Status; Male; Pregnancy; Radiation-Protective Agents; Rats; Rats, Wistar; Semen Analysis; Seminiferous Epithelium; Sexual Maturation; Testicular Diseases